Resonant tunneling diode terahertz sources with up to 1 mW output power in the J-band - Al-Khalidi, Abdullah; Alharbi, Khalid Hamed; Wang, Jue; Morariu, Razvan; Wang, Liquan; Khalid, Ata; Figueiredo, José M. L.; Wasige, Edward (IEEE, 2019)
Terahertz (THz) oscillators based on resonant tunneling diodes (RTDs) have relatively low output power, tens to hundreds of microwatts. The conventional designs employ submicron-sized RTDs to reduce the device self-capacitance and, as a result, realize higher oscillation frequencies. However, reducing the RTD device size leads to lower output power. In this article, we present RTD oscillators that can employ one or two RTD devices of relatively large size, 9-25 μm2, for high power and, at the same time, can oscillate at THz frequencies. This is achieved through low resonating inductances realized by microstrip or coplanar waveguide transmission line short stubs with low characteristic impedances (Z0), which have lower inductance values per unit length and so compensate the increase of the self-capacitance of large area RTD devices. Thus, fabrication using only photolithography is possible. It is also shown that device sizing, which is limited only by bias stability considerations, does not limit device bandwidth. Further, we report a new way to estimate the RTD oscillator output power with frequency. A series of oscillators with oscillation frequencies in the 245-309 GHz range and output powers from 0.1 to 1 mW have been demonstrated showing the feasibility of the proposed approach.
Keywords: Photolithography; resonant tunneling diode (RTD); terahertz (THz) sources